Virulence of entomopathogenic nematodes (Rhabditida: Steinernematidae and Heterorhabditidae) for the control of Diabrotica speciosa germar (coleoptera: chrysomelidae) - Santos,Viviane (2011)
Entomopathogenic nematodes (EPNs) are used in biological control of soil insects and show promise in the control of D. speciosa. The objective of this work was to evaluate the potential of native and exotic entomopathogenic nematode isolates in the control of D. speciosa under laboratory and greenhouse conditions. Results showed that all of EPNs caused larval mortality. The most virulent were Heterorhabditis sp. RSC01 (94%), Steinernema glaseri (84%), Heterorhabditis sp. JPM04 (82%) and Heterorhabditis amazonensis RSC05 (78%). There was no effect of the Heterorhabditis sp. RSC01 and S. glaseri isolates on eggs. The maximum mortality of D. speciosa larvae by Heterorhabditis sp. RSC01 was observed at a concentration of 300 IJ/ insect, while by S. glaseri observed the highest mortality at the concentration of 200 IJ/ insect. The Heterorhabditis sp. RSC01 isolate caused over 80% pupal mortality at a concentration of 250 IJ/insect. The virulence of Heterorhabditis sp. RSC01 and S. glaseri was affected by temperature. The Heterorhabditis sp. RSC01 isolate caused reduction in larva survival under greenhouse conditions at all of the tested concentrations and there was no difference in mortality among different concentrations of infectid juveniles.